2003
DOI: 10.1038/sj.gt.3302138
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the splice acceptor for improved gene expression and viral titer in an MLV-based retroviral vector

Abstract: We have recently developed a retroviral vector that contains a splice acceptor from the human EF1-a gene and drives a significantly higher level of gene expression than other well known murine leukemia virus-based vectors. However, one downside of this vector is that viral titer significantly varies depending on the packaging lines used. Results from Northern blot analysis indicated that in certain cell lines the genomic transcript containing the packaging signal sequence was too efficiently spliced to the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…pEQ273 contains the full genomic sequence of IE1, including the HCMV major immediate-early promoter, while pEQ336 having only the promoter and lacking the coding sequence as described (Biegalke and Geballe, 1991). The retroviral vector, MT5-cIE1, was constructed by inserting the cDNA sequence of IE1 into retroviral vector MT5 (Lee et al, 2004). The reporter plasmid, pCN-chloramphenicol acetyl transferase (CAT), were constructed by inserting the CAT gene into expression vector pCN (Lee et al, 2000).…”
Section: Materials and Methods Cell Cultures And Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…pEQ273 contains the full genomic sequence of IE1, including the HCMV major immediate-early promoter, while pEQ336 having only the promoter and lacking the coding sequence as described (Biegalke and Geballe, 1991). The retroviral vector, MT5-cIE1, was constructed by inserting the cDNA sequence of IE1 into retroviral vector MT5 (Lee et al, 2004). The reporter plasmid, pCN-chloramphenicol acetyl transferase (CAT), were constructed by inserting the CAT gene into expression vector pCN (Lee et al, 2000).…”
Section: Materials and Methods Cell Cultures And Plasmidsmentioning
confidence: 99%
“…6A). The cDNA sequence of IE1 was inserted into retroviral vector MT5 (Lee et al, 2004). Cell-free retroviral vectors were prepared by the three-plasmid transfection method and used to transduce U373MG cells.…”
Section: Effects Of Transient Expression Of Ie1 Proteinmentioning
confidence: 99%
“…21 Briefly, an HIV-1-LTR-MazF-polyA cassette was introduced in the direction opposite of the MoMLV-LTR at the multiple cloning site of the retroviral vector plasmid pMT. 36 The Δ LNGFR gene 37 was introduced into the retrovirus vector as a surface marker. The Δ LNGFR gene is under the control of the human phosphoglycerate kinase (PGK) promoter.…”
Section: Methodsmentioning
confidence: 99%
“…Such a relatively strong PPT can substitute for either a weak branch point or poor sequence conservation of the actual 3Јss (35). Moreover, introducing a very efficient cellular 3Јss into MLV vectors did not fully prevent the formation of genomic RNA (15). Finally, when constructing a new generation of retroviral self-inactivating vectors, we placed the internal promoter 18 bp downstream of the PBS and thus 24 bp upstream of the 5Јss.…”
Section: Discussionmentioning
confidence: 99%
“…The polypyrimidine tract (PPT), a second key feature of all 3Јss, is of suboptimal length (10 nucleotides long when compared with 13 residues in average) but not interrupted by weakening purines as most PPTs of HIV (14). Interestingly, a recent study showed that in the context of MLV-based retroviral vectors, the 3Јss can be replaced by very efficient counterparts derived from the human EF1␣ gene (15). Although the infectious titer was reduced by about 1 order of magnitude, unspliced genomic RNA was still formed, arguing for the existence of additional splice inhibitory sequences.…”
mentioning
confidence: 99%